Przestrzenne i czasowe zróżnicowanie amplitud stanów wody jezior w Polsce w latach 1981–2015 - Plewa, Katarzyna; Wrzesiński, Dariusz; Baczyńska, Alicja (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2017)
The objective of the paper is the determination of the value and spatial variability of monthly and annual amplitudes of water stages in Polish lakes. The study applied daily values of water stages of 74 lakes located in Polish lakelands. Mean, maximum, and extreme amplitudes of water stages were calculated for each month and year in the period 1981-2015. The study revealed similar spatial distribution of isoamplitudes. Considerably higher amplitudes, however, both monthly and annual, occurred in coastal lakes and in the central part of the lakeland belt from Gopło to Druzno.
Keywords: amplitudes; water stage; lake; Poland